Homoeologous Chromosomes From Two Hordeum Species Can Recognize and Associate During Meiosis in Wheat in the Presence of the Ph1 Locus - Calderón, María C.; Rey, María-Dolores; Martín, Antonio; Prieto, Pilar (Frontiers in Plant Science, 2018)
Understanding the system of a basic eukaryotic cellular mechanism like meiosis is of fundamental importance in plant biology. Moreover, it is also of great strategic interest in plant breeding since unzipping the mechanism of chromosome specificity/pairing during meiosis will allow its manipulation to introduce genetic variability from related species into a crop. The success of meiosis in a polyploid like wheat strongly depends on regular pairing of homologous (identical) chromosomes and recombination, processes mainly controlled by the Ph1 locus. This means that pairing and recombination of related chromosomes rarely occur in the presence of this locus, making difficult wheat breeding trough the incorporation of genetic variability from related species. In this work, we show that wild and cultivated barley chromosomes associate in the wheat background even in the presence of the Ph1 locus. We have developed double monosomic wheat lines carrying two chromosomes from two barley species for the same and different homoeology chromosome group, respectively. Genetic in situ hybridization revealed that homoeologous Hordeum chromosomes recognize each other and pair during early meiosis in wheat. However, crossing over does not occur at any time and they remained always as univalents during meiosis metaphase I. Our results suggest that the Ph1 locus does not prevent chromosome recognition and pairing but crossing over between homoeologous. The role of subtelomeres in chromosome recognition is also discussed.